2002
DOI: 10.1002/path.1121
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor E2F‐1 acts as a growth‐promoting factor and is associated with adverse prognosis in non‐small cell lung carcinomas

Abstract: Numerous upstream stimulatory and inhibitory signals converge to the pRb/E2F pathway, which governs cell-cycle progression, but the information concerning alterations of E2F-1 in primary malignancies is very limited. Several in vitro studies report that E2F-1 can act either as an oncoprotein or as a tumour suppressor protein. In view of this dichotomy in its functions and its critical role in cell cycle control, this study examined the following four aspects of E2F-1 in a panel of 87 non-small cell lung carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
169
0
23

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(206 citation statements)
references
References 75 publications
14
169
0
23
Order By: Relevance
“…Although a genuine tumour-derived somatic cell mutation in E2F-1 has recently been described and the investigation of its activities could indeed prove rewarding, the lack of a panel of E2F-1 mutants makes discerning the role of E2F in tumour development more difficult to determine. 84 While the continued study of E2F-1-induced cell death will provide an insight on this issue, it must ultimately be kept in mind that although E2F lies at the core of very significant cell fate decisions, it forms only part of a complex matrix of cell signalling events and interactions. For example, a recent study looking at the role of E2F-1 in the response of keratinocytes to UVB irradiation in mouse skin unexpectedly showed that E2F1 À/À mice exhibit enhanced apoptosis following exposure to UVB when compared to wild-type counterparts.…”
Section: Future Prospectsmentioning
confidence: 99%
“…Although a genuine tumour-derived somatic cell mutation in E2F-1 has recently been described and the investigation of its activities could indeed prove rewarding, the lack of a panel of E2F-1 mutants makes discerning the role of E2F in tumour development more difficult to determine. 84 While the continued study of E2F-1-induced cell death will provide an insight on this issue, it must ultimately be kept in mind that although E2F lies at the core of very significant cell fate decisions, it forms only part of a complex matrix of cell signalling events and interactions. For example, a recent study looking at the role of E2F-1 in the response of keratinocytes to UVB irradiation in mouse skin unexpectedly showed that E2F1 À/À mice exhibit enhanced apoptosis following exposure to UVB when compared to wild-type counterparts.…”
Section: Future Prospectsmentioning
confidence: 99%
“…All together, these studies strongly suggest an important role(s) of RB family members in lung cancer progression. Different studies showed that three genes downstream from the pRb pathway that support cell growth, E2F, DP-1, and HDAC, are overexpressed in lung adenocarcinomas (Chang and Szabo, 2002;Gorgoulis et al, 2002;Singhal et al, 2003a). The expression of these Rb-dependent genes is increased probably because upregulation of cyclin D1 and cyclin D2, key regulators of pRb phosphorylation, and downregulation of cyclin-dependent kinase inhibitors p15, p21, p19, and p57 (Kawamata et al, 1995;Rusin et al, 1996;Gazzeri et al, 1998;Keum et al, 1999;Jin et al, 2001;Shoji et al, 2002;Singhal et al, 2003a).…”
Section: The Cell-cycle Machinery and Lung Cancermentioning
confidence: 99%
“…In mammals, the E2F family has six different members. The best-characterised member is E2F-1 and its over-expression has been shown to be strongly associated with lung carcinogenesis [55]. The ability of E2F-1 to stimulate transcription appears to be subjected to multiple regulations including co-activation by CBP/p300 and reversal of Rb-mediated repression through Rb phosphorylation [55].…”
Section: Potential Therapeutic Approachesmentioning
confidence: 99%
“…The best-characterised member is E2F-1 and its over-expression has been shown to be strongly associated with lung carcinogenesis [55]. The ability of E2F-1 to stimulate transcription appears to be subjected to multiple regulations including co-activation by CBP/p300 and reversal of Rb-mediated repression through Rb phosphorylation [55]. At a molecular level, the Cdk-stimulated interaction of CBP/p300 with E2F-1 may be involved in irreversibly committing cells to cell-cycle progression [56].…”
Section: Potential Therapeutic Approachesmentioning
confidence: 99%